Dampak Pembelajaran Daring Jangka Panjang terhadap Siswa dan Guru (Studi Kasus SMKN 1 Godean, Yogyakarta) - Fitri Ramadhani; Adini Nur Azizah; Alfi Nur Hidayati (Edumaspul: Jurnal Pendidikan, 2022)
AbstractThis research was conducted when the Covid-19 pandemic in Indonesia had occurred over the past year. The existence of pandemic forced the learning systems around the world to change into online learning in order to make safer and more efficient for everyone that involved. However, there are several impacts arise when online learning happened for the long-term. The research discussed about the various impact of long-term online learning, especially on students and teachers from the Vocational High School (SMKN) 1 Godean, Yogyakarta. This research covers (1) the impact of long-term online learning for students; (2) the impact of long-term online learning for teachers. There were 25 student and six teacher respondents from SMKN 1 Godean. The data was collected online using close questionnaire technique. The data analysis technique used quantitative descriptive statistics. The results showed, there is more than 60% of students agreed that long-term online learning brings an impact on them. Additionally, more than 50% of teachers agree that long-term online learning brings impacts on them.